KOMPETENSI SPIRITUAL PENDIDIK (Suatu Kajian pada Unsur Kalbu) - Zulfatmi Zulfatmi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2017)
Education is a process of fostering physical and spiritual, so that educators who have multi-competence education: paedagogi; personal; social and spiritual. Spiritual competence can be enhanced by improving the quality of the heart. Qalbu potentially good has characteristics such as mentioned in the Quran: qalbun saliim; qalbun muniib; qalbun muallafun; qalbun muthmainnun; taqwal qulub; sakiinah's heart; and ra'fatul qalbi warahmatuh. On the other hand, qalbu must also be preserved from the character which makes it hardened like a stone so it is difficult to obtain guidance from Allah SWT, ie atsimun qalbuhu; ghillun fi al qalbi; man aghfalna qalbuhu. The educator who constantly improves his spiritual competence by reviving the good character of his qalbunya will be easier to realize the ideals of education more effectively, because he is in harmony with the direction and target desired Rabbnya.